A new species of Valgothrombium Willmann, 1940, with additional taxonomic data for Valgothrombiinae genera known as larvae (Acari: Prostigmata: Microtrombidiidae) - Mąkol, Joanna; Łaydanowicz, Joanna (Zootaxa, 2010)
Valgothrombium mariae sp. nov. is described based on larvae collected in Norway. The generic diagnosis for larvae of Valgothrombium is modified and the taxonomy of Valgothrombiinae genera known as larvae discussed. Boletitrombium Saboori, Ueckermann & van Harten, 2007 is considered a junior synonym of Valgothrombium. Genera currently assigned to Valgothrombiinae and species belonging to genera known as larvae are listed. A key to world species of Valgothrombiinae known from larvae is provided.